2019
DOI: 10.1101/756411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-definition of claudin-low as a breast cancer phenotype

Abstract: The claudin-low breast cancer subtype is defined by gene expression characteristics and encompasses a remarkably diverse range of breast tumors. Here, we investigate genomic, transcriptomic, and clinical features of claudin-low breast tumors. We show that claudin-low is not simply a subtype analogous to the intrinsic subtypes (basal-like, HER2-enriched, luminal A, luminal B and normal-like) as previously portrayed, but is a complex additional phenotype which may permeate brea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…To determine whether high expression of the GLIS2 signature is a hallmark of claudin-low tumors across breast cancers in general, we compared the expression of GLIS2 target genes in 1082 breast cancers, using a public dataset from The Cancer Genome Atlas (TCGA) (38). We found that high expression of GLIS2 target genes enables the segregation of claudin-low tumors from other breast tumors in a manner similar to the Prat et al (37) reference panel of genes used to mark claudin-low cancers (Fig.…”
Section: Primary Cilium-dependent Regulation Of Glis2 Controls Claudin-low Matic Stemness and Tumorigenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether high expression of the GLIS2 signature is a hallmark of claudin-low tumors across breast cancers in general, we compared the expression of GLIS2 target genes in 1082 breast cancers, using a public dataset from The Cancer Genome Atlas (TCGA) (38). We found that high expression of GLIS2 target genes enables the segregation of claudin-low tumors from other breast tumors in a manner similar to the Prat et al (37) reference panel of genes used to mark claudin-low cancers (Fig.…”
Section: Primary Cilium-dependent Regulation Of Glis2 Controls Claudin-low Matic Stemness and Tumorigenicitymentioning
confidence: 99%
“…For gene expression analysis across breast tumor subtypes, the pipeline from Fougner et al (38) was used on the TCGA-BRCA Dataset (github.com/clfougner/ClaudinLow). For ChIP-seq analysis, previously reported genome-wide murine Snail binding sites elucidated using ChIP-seq were obtained from the GEO (GSE61198).…”
Section: Gene Expression and Chip-seq Analysesmentioning
confidence: 99%
“…This phenotype involves various intrinsic subtypes associated with high immune and stromal infiltration levels and a low mutation burden, proliferation, and genomic instability. 14…”
Section: Introductionmentioning
confidence: 99%
“…Third, the spatially heterogenous distribution of WTP+ and WTP-niches at primary tumor periphery parallels the enrichment of post-EMT cells at tumor invasion fronts (39) and heterogeneous EMT transition states localized in different niches (40). Fourth, human residual breast cancers resistant to neoadjuvant ET (letrozole) or CT (docetaxel) display mesenchymal and tumor-initiating features correlative with poor prognosis (41), even though the corresponding gene expression marker was linked to a specific type of molecular subtype (-claudin-low‖) rather than a pan-cancer marker independent of breast cancer molecular subtyping (42). Despite these lines of indirect evidence, the ultimate confirmation of the EMT nature of WTP will require changes in a set of molecular markers and cellular properties (43) to synchronize with the WTP marker of 2.8-mm niche-scale extracellular matrix remodeling (44).…”
Section: Discussionmentioning
confidence: 99%